Exploring the paths between dysfunctional attitudes towards motherhood and postpartum depressive symptoms: The moderating role of self-compassion. - Fonseca, Ana (2017)
Better understanding how cognitive processes operate to influence women’s depressive symptoms during the postpartum period is crucial for informing preventive and treatment approaches. The present study aimed to examine the relationship between women’s dysfunctional attitudes towards motherhood and depressive symptoms, considering the mediating role of negative automatic thoughts and the moderating role of self-compassion. A sample of 387 women in the postpartum period cross-sectionally answered a set of questionnaires to assess dysfunctional attitudes towards motherhood, negative automatic thoughts (general and postpartum-specific), depressive symptoms and self-compassion. Women with clinically significant depressive symptoms presented more dysfunctional attitudes towards motherhood, more frequent negative thoughts and lower self-compassion. More dysfunctional beliefs about others’ judgments and about maternal responsibility were associated with higher depressive symptoms, and this effect occurred through both general and postpartum-specific thoughts related to the metacognitive appraisal of the thought content. Moreover, these relationships occurred only when women presented low or moderate levels of self-compassion. These results highlight the need to comprehensively assess women’s cognitive variables during the postpartum period with appropriate measures, for the early identification of women with more dysfunctional beliefs about motherhood, who may be at higher risk of depression. Moreover, preventive/treatment approaches should aim not only to challenge women’s pre-existing dysfunctional beliefs but also to promote a more self-compassionate attitude towards themselves.